Relationship Between Sequence Homology, Genome Architecture, and Meiotic Behavior of the Sex Chromosomes in North American Voles. Issue 1 (12th July 2018) - Dumont, Beth L; Williams, Christina L; Ng, Bee Ling; Horncastle, Valerie; Chambers, Carol L; McGraw, Lisa A; Adams, David; Mackay, Trudy F C; Breen, Matthew
Abstract: On the heterogametic sex chromosomes, the homology-driven processes of pairing, recombination, and segregation are restricted to a short region of X/Y homology known as the pseudoautosomal region (PAR). Although failure of X/Y associations in most mammals... In most mammals, the X and Y chromosomes synapse and recombine along a conserved region of homology known as the pseudoautosomal region (PAR). These homology-driven interactions are required for meiotic progression and are essential for male fertility. Although the PAR fulfills key meiotic functions in most mammals, several exceptional species lack PAR-mediated sex chromosome associations at meiosis. Here, we leveraged the natural variation in meiotic sex chromosome programs present in North American voles ( Microtus ) to investigate the relationship between meiotic sex chromosome dynamics and X/Y sequence homology. To this end, we developed a novel, reference-blind computational method to analyze sparse sequencing data from flow-sorted X and Y chromosomes isolated from vole species with sex chromosomes that always ( Microtus montanus ), never ( Microtus mogollonensis ), and occasionally synapse ( Microtus ochrogaster ) at meiosis. Unexpectedly, we find more shared X/Y homology in the two vole species with no and sporadic X/Y synapsis compared to the species with obligate synapsis. Sex chromosome homology in the asynaptic and occasionally synaptic species is interspersed along chromosomes and largely restricted to low-complexity sequences, including a striking enrichment for the telomeric repeat sequence, TTAGGG. In contrast, homology is concentrated in high complexity, and presumably euchromatic, sequence on the X and Y chromosomes of the synaptic vole species, M. montanus . Taken together, our findings suggest key conditions required to sustain the standard program of X/Y synapsis at meiosis and reveal an intriguing connection between heterochromatic repeat architecture and noncanonical, asynaptic mechanisms of sex chromosome segregation in voles.